Tinjauan Yuridis Kepres No. 55 Tahun 1993 Tentang Pengadaan Tanah Bagi Pelaksanaan Pembangunan Untuk Kepentingan Umum dan Pelaksanaannya - Maria S.W. Sumardjono (Magister Administrasi Publik, 1996)
Necessity will make available land for developmcw, offering the opportunity for the transfer of for several projects. whether for state of public requirements, or for business necessity tfar that matter. in either a small or a large scale. Because the slate owned land is no longer satisfactoo, in supply. it is desirable that these various necessities for land, which in a way. are objects for the need for the right to prossess land. whether it as individuals or by a legal body, or by the legal community radar) be there. Regulating or controlling this aspect is not that easy. This is because there often en:curs a discrepancy between das sullen and das rein. This writing will attempt to analyze the implementation of the kepres No. 55 of 1993 whose operationalization was supported by the ministerial regulation Agrarian/Head of BPN No. 1 of 1994, by revising what was meant by public importance. how its deliberation should be executed in the process of-freeing land, how the loss should be shared, how the prcession of the transferred land should be in the hands of the legal community (adat). From the results of the analysis. it is concluded that the concept of public importance, the discussion and sharing the loss, all eAperience a shift. With the validity of the kepres discussed above, it is apparent that it is only government which has the right to use the land meant for public importance for other development activities.